KEWAJIBAN PEMBERITAHUAN AKUSISI PERUSAHAAN KEPADA KOMISI PENGAWAS PERSAINGAN USAHA (Studi Putusan Nomor 02/Pdt.Sus-KPPU/2021/PN Niaga Jkt.Pst) - Abdul Jamil Sarifuddin (2023)
The background for writing this thesis was due to a decision by the Commercial Court at the Central Jakarta District Court (Decision Number 02/Pdt.Sus-KPPU/2021/PN Niaga Jkt.Pst). PT. Housing Development which has made the Acquisition of PT. Centurion Iman Perkasa filed a lawsuit due to objections to the decision of the Business Competition Supervisory Commission. The formulation of the problem in this thesis is what is the basis for the judge's consideration of rejecting PT. Housing Development against the decision of the business competition supervisory commission notifying company acquisitions and how the implementation of company acquisitions provides legal certainty. The research method used in writing this thesis is the normative juridical law research method. Based on these two problems, it can be concluded that the judge's consideration of rejecting PT. Housing Development, namely based on article 28 and article 29 of law number 5 of 1999 and government regulation number 57 of 2010. Meanwhile, the implementation of company acquisitions that provide legal certainty, namely according to researchers, the rules in law number 5 of 1999 and government regulations number 57 of 2010 still provide broad interpretation space that can lead to conflicts in the future, so according to researchers there must be legal renewal in regulating corporate takeover or acquisition.